Smart cities: effects on health, work and governance - Jonatas Dutra Sallaberry; Edicreia Andrade dos Santos; Leonardo Flach (Innovation & Management Review, 2025)
This study investigates the effects of smart technologies in urban management on the economic and social dimensions of Brazilian Smart Cities, with a focus on fiscal governance, health, and work. Smart Cities are defined as those that integrate systems, processes, and services through enabling and inclusive technologies that benefit the community.Grounded in Smart City literature, this empirical study examines the influence of smart technologies on health and work indicators, mediated by fiscal governance. Secondary data from 93 Brazilian Smart Cities were analyzed using structural equation modeling, incorporating mediating effects.The results indicate that smart technologies positively influence work indicators but do not directly affect health indicators. A positive relationship with health indicators emerges only when mediated by fiscal governance, underscoring the limitations of merely providing technology in Smart Cities.Cities with stronger fiscal capacity are better equipped to invest in the tools, personnel, and infrastructure necessary for the effective implementation of health technologies. These findings can help policymakers allocate resources more strategically to benefit the population.This study provides empirical evidence on key social components that must be developed for a Smart City to truly serve its citizens. It demonstrates that technology alone has limited impact, but when combined with effective public policy, it can significantly enhance critical indicators such as public health.
Keywords: 650; Smart cities; Health; Work; Urban management; Fiscal governance